Perceiving, reporting and managing an injury - perspectives from national team football players, coaches and health professionals - Vella, S.; Bolling, C.; Verhagen, E.; Moore, I. S. (British Journal of Sports Medicine, 2021)
Background Injury perceptions and related risk-mitigating interventions are context-dependent. Despite this, most injury surveillance systems guided by established consensus statements are not context-specific as they do not integrate stakeholders` perspectives. Accordingly, to address the injury problem in context, injury surveillance systems need to be aligned with the stakeholders` injury perceptions and practices related to its reporting and management.